Animals that live in the sea - Straker, Joan Ann, 1943- ([Washington] : National Geographic Society, 1978)
An introduction to the characteristics and natural environment of a variety of creatures inhabiting the ocean.
Keywords: Marine animals -- Juvenile literature; Marine animals